Modelo evolutivo del impacto de técnicas VaR en los mercados financieros; Evolutionary model of the impact of VaR techniques on financial markets - Bàrbara Llacay; Gilbert Peffer (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– In recent years, some authors have warned of the increasingly widespread use of risk management techniques by financial institutions, arguing that this can cause the market to become more unstable. To analyse these claims, we present a model based on evolutionary game theory of a financial market, where part of the investors use the VaR technique to manage their risk. We study the evolution of this market through simulation, and we confirm that the use of risk management models can induce instability regimes in the market, characterised by sudden changes in the asset price and sharp increases in the volatility.
Keywords: C63; C73; G01; G10; 330; Risk management; VaR; Evolutionary game theory; Financial markets